Bioactive composition and TLC profile data on PAX herbal health tea and PAX herbal diatea - Ayobami Owolabi, Tunde; Amodu, Emmanuel (International Journal of Advanced Chemistry, 2022)
Background: The phytoconstituents of herbal drugs are largely influenced by the quality control system used during and post-production processes including the handling of such products. Thin Layer Chromatography is one of such quality control parameters that demonstrate uniqueness and uniformity between various substances, serving as an identity for such substances.Â  Pax Herbal Health tea (PHT) and Pax Herbal Diatea (PDT) are polyherbal drugs, PHT is used as a tonic for general wellness, while, PDT is used in the management and treatment of diabetes. This study evaluated the different phytoconstituents present and developed Thin-layer chromatography (TLC) fingerprint profiles for PHT and PDT to serve as quality control checks during the production for consistency and market uniqueness after production.Material and Methods: Qualitative phytochemical and chromatographic analyses were carried out using standard methods.Results: The phyto-screening revealed the presence of Alkaloid, Flavonoid, Tanin, Terpenoids, Reducing sugar, Steroid, and Cardiac glycoside in PHT while, Saponin, Tanin, Steroids, Reducing sugar, Flavonoid, and Terpenoids were observed in PDT. The TLC finger-print chromatograms of PHT after development with n-Hexane:Ethyl acetate (3:2) showed four distinct components under ultraviolet light at 365 nm, and three spots when sprayed with 20% methanolic sulphuric under visible light, while, PDT developed in n-Hexane:ethyl acetate:methanol (2.5:2:0.5) revealed three fluorescent components at 365 nm and four components after sulphuric acid treatment.Conclusion: From this present study, identity cards have been designed for PHT and PDT through bioactive composition and TLC profiles which can be used in accessing the quality and consistency of the herbal drugs.Â Â